STRATEGI PEMBELAJARAN ASHWAT ARABIYAH DAN MUFRADAT - Rizka Widayanti (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2016)
The purpose of the research is to discuss the teaching strategy of Arabic. Teaching strategy is an important component in teaching languages, including Arabic. The suitable strategy in teaching Arabic is based on the material and the condition of the students. Enjoyable or not the process of teaching and learning Arabic would determine the result expected of the teaching itself. If the beginning of the process of teaching and learning has already implemented an active and joyful strategy, the students will be interested in the process of learning Arabic. Arabic learning is focusing on creating various conditions in which it enables the students to utilize their time to study. The teacher in the concept of learning will no longer as the main source who transfers knowledge to the students. Active learners place the teacher as a facilitator who creates a conducive class to make the process of teaching and learning be better. It is similar to the phoneme learning of phoneme and vocabulary. Phonology is a way to pronounce Arab letters fluently and accurately whether they are pronounced separately as the letter itself or after it is combined and based on the need. It is also the same as vocabulary. It is one of language components that foreign language learners must-have. It is included in Arabic.